Manajemen Madrasah dalam Mewujudkan Pendidikan Karakter Peserta Didik di MTs Negeri Bondowoso II - Hidayat, Fitri Nur; Karyodiputro, Muhammad Ikrom (Universitas Nurul Jadid, 2019)
The focus of this research is how the madrasah management process includes planning, organizing, implementing, and monitoring in realizing character education for students at MTsN Bondowoso II? The purpose is to describe the process of planning, organizing, implementing, and supervising madrasas in realizing character education for students at MTsN Bondowoso II. This study uses a qualitative approach, with descriptive analysis methods. Data collection is done by using quasi observation techniques, participation, interview and documentation. Data analysis techniques used are data reduction, data presentation, and conclusion. Checking the validity of the findings is done by means of peer discussion and triangulation techniques that use source triangulation and methods/techniques. The results of this study that madrasah management process in realizing character education at MTsN Bondowoso II was implemented through four aspects/four management functions, namely planning in the form of a madrasah activity program plan, organizing in the form of division of tasks for all teachers and madrasah staff to realize the program activities, implementation in the form of implementation from the program plan for madrasah activities, and supervision in the form of evaluating all performance in implementing the madrasah program, which are four aspects integrated with character values that can be used as role models for students. Keywords: Madrasah Management, Character Education.